2013
DOI: 10.1097/scs.0b013e3182801eb0
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Reconstruction of a Palatomaxillary Defect With Nonvascularized Fibula Bone Graft and Distraction Osteogenesis

Abstract: Reconstruction of extensive palatomaxillary defects with oronasal/antral communication represents a challenge to surgeons. Bone-containing microvascular flaps have been suggested as a promising option for rehabilitation of function and esthetics. These types of flaps, however, might be associated with high morbidity. A combination of less complicated treatments might also provide acceptable results while diminishing potential donor site complications. This clinical report presents a bilateral maxillary defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The maxilla is the major structure of the midface, it is essential for esthetic and functions of the midface. It is a tooth-bearing area, a supporting structure for midfacial soft tissues and a separating barrier between oral and sinonasal cavities [6]. Maxillary reconstruction must restore all the bone, skin and mucosal structures.…”
Section: Discussionmentioning
confidence: 99%
“…The maxilla is the major structure of the midface, it is essential for esthetic and functions of the midface. It is a tooth-bearing area, a supporting structure for midfacial soft tissues and a separating barrier between oral and sinonasal cavities [6]. Maxillary reconstruction must restore all the bone, skin and mucosal structures.…”
Section: Discussionmentioning
confidence: 99%
“…This is more obvious when an evidence-based decision is made according to all data presented in the literature. Parameters which can describe alveolar bony defects are: • Defect base width and number of residual bony walls surrounding the defect Anterior and posterior parts of the mandible and maxilla have different bone qualities; hence they have different regenerative capacities [7]. The length of the defect affects the degree of vascularization.…”
Section: Recipient Site Classification and Defect Analysismentioning
confidence: 99%
“…In vertical defects with no sufficient width to accept implants, the augmentation procedure becomes complicated because both dimensions require restoration [8]. It has been suggested that a wide bony defect base has greater capacity for bone regeneration compared to a narrow base defect [7]. The number of surrounding bony walls around the defect is mentioned in the literature as stabilization for the initial blood clot [8].…”
Section: Recipient Site Classification and Defect Analysismentioning
confidence: 99%
See 1 more Smart Citation